2D Materials: Re Doping in 2D Transition Metal Dichalcogenides as a New Route to Tailor Structural Phases and Induced Magnetism (Adv. Mater. 43/2017). Issue 43 (14th November 2017) - Kochat, Vidya; Apte, Amey; Hachtel, Jordan A.; Kumazoe, Hiroyuki; Krishnamoorthy, Aravind; Susarla, Sandhya; Idrobo, Juan Carlos; Shimojo, Fuyuki; Vashishta, Priya; Kalia, Rajiv; Nakano, Aiichiro; Tiwary, Chandra Sekhar; et al.
Abstract : In article number1703754, Aravind Krishnamoorthy, Chandra Sekhar Tiwary, Pulickel M. Ajayan, and co‐workers show that Re‐doping of transition‐metal‐dichalcogenide monolayers during chemical vapor deposition (CVD) offers a simple way to controllably tune crystal structure and phase composition in two‐dimensional alloys. The CVD‐synthesized MoReSe2 alloys show composition‐dependent electronic structures and magnetic properties.